MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN DENGAN PERSPEKTIF LINGKUNGAN: SOLUSI UNTUK TANTANGAN GLOBAL - Rahmat, Hayatul Khairul (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
Sustainable development has become a pressing global issue in recent decades, with a primary focus on balancing economic growth, social well-being, and environmental sustainability. The environment plays a crucial role in achieving sustainable development, as finite natural resources must be managed wisely to ensure the well-being of future generations. This paper discusses the importance of integrating sustainability principles into development, emphasizing the interlinked ecological, social, and economic dimensions. The study also explores various policies and approaches that can be implemented to address the challenges of sustainable development, along with the importance of environmental education and awareness in society. In conclusion, achieving sustainable development requires collaboration between the government, private sector, and society to preserve the environment while supporting inclusive economic growth.